Cloud-controlled microscopy enables remote project-based biology education in underserved Latinx communities. Issue 11 (November 2022) - Baudin, Pierre V.; Sacksteder, Raina E.; Worthington, Atesh K.; Voitiuk, Kateryna; Ly, Victoria T.; Hoffman, Ryan N.; Elliott, Matthew A.T.; Parks, David F.; Ward, Rebecca; Torres-Montoya, Sebastian; Amend, Finn; Montellano Duran, Natalia; et al.
Abstract: Project-based learning (PBL) has long been recognized as an effective way to teach complex biology concepts. However, not all institutions have the resources to facilitate effective project-based coursework for students. We have developed a framework for facilitating PBL using remote-controlled internet-connected microscopes. Through this approach, one lab facility can host an experiment for many students around the world simultaneously. Experiments on this platform can be run on long timescales and with materials that are typically unavailable to high school classrooms. This allows students to perform novel research projects rather than just repeating standard classroom experiments. To investigate the impact of this program, we designed and ran six user studies with students worldwide. All experiments were hosted in Santa Cruz and San Francisco, California, with observations and decisions made remotely by the students using their personal computers and cellphones. In surveys gathered after the experiments, students reported increased excitement for science and a greater desire to pursue a career in STEM. This framework represents a novel, scalable, and effective PBL approach that has the potential to democratize biology and STEM education around the world. Abstract : STEM education; Cloud laboratories; Remote education; Biology education; Latinx; Hispanics; Undeserved communities